Effectiveness of Bitter melon (Momordica charantia L) Extract on Growth of Trichopyton rubrum: In Vitro Study - Vika Pangesty; Ika Dyah Kurniati; Kanti Ratnaningrum (MAGNA MEDIKA: Berkala Ilmiah Kedokteran dan Kesehatan, 2023)
Trichophyton rubrum is type of fungus that most often causes superficial fungal infections. Development of herbal ingredients as antifungal therapy is carried out to find alternative therapies for fungal infections. Bitter melon contains various compounds that have potential to be used as antifungals, including flavonoids and saponins. The aim of this study was to determine the effect of bitter melon extract (Momordica charantia L) on the growth of Trichopyton rubrum. This study used bitter melon extract at concentrations of 5%, 25%, 50%, 75% and 100%. Ketoconazole concentrations of 2% was used as a positive control. Pure cultures of Trichopyton rubrum were diluted using physiological NaCl. Fungal growth was observed microscopically and macroscopically. Results showed that Trichopyton rubrum grew at a concentration of 5% while at concentrations of 25%, 50%, 75% and 100% there was no Trichopyton rubrum growth. Bitter melon extract at a concentration of 25% had similar effect as ketoconazole 2%. Conclusion Bitter melon extract at concentrations of 25%, 50%, 75% and 100% had a similar effect to 2% ketoconazole in inhibiting the growth of Tricophyton rubrum.